2020
DOI: 10.1002/jcsm.12541
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐3 deficiency associated with the dystrophy P104L mutation impairs skeletal muscle mitochondrial form and function

Abstract: Background Caveolin‐3 (Cav3) is the principal structural component of caveolae in skeletal muscle. Dominant pathogenic mutations in the Cav3 gene, such as the Limb Girdle Muscular Dystrophy‐1C (LGMD1C) P104L mutation, result in substantial loss of Cav3 and myopathic changes characterized by muscle weakness and wasting. We hypothesize such myopathy may also be associated with disturbances in mitochondrial biology. Herein, we report studies assessing the effects of Cav3 deficiency on mitochondrial form and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…The Ca 2+ released from the ER stimulates pyruvate dehydrogenase in mitochondria and the F0/F1-ATPase required for ATP synthesis, Krebs cycle, and pyruvate decarboxylation [ 113 , 114 ]. Shah et al [ 115 ] have revealed that Cav3 deficiency in cardiac muscle cells associated with the Cav3P104L mutation invokes major disturbances in mitochondrial respiration and energy status that may contribute to the pathology of RMD-2. The targeting of Cav3 to mitochondria improves the function of mitochondria and thus induces stress adaptation in the heart.…”
Section: Function Of Caveolin-3 In Mitochondrial Homeostasismentioning
confidence: 99%
“…The Ca 2+ released from the ER stimulates pyruvate dehydrogenase in mitochondria and the F0/F1-ATPase required for ATP synthesis, Krebs cycle, and pyruvate decarboxylation [ 113 , 114 ]. Shah et al [ 115 ] have revealed that Cav3 deficiency in cardiac muscle cells associated with the Cav3P104L mutation invokes major disturbances in mitochondrial respiration and energy status that may contribute to the pathology of RMD-2. The targeting of Cav3 to mitochondria improves the function of mitochondria and thus induces stress adaptation in the heart.…”
Section: Function Of Caveolin-3 In Mitochondrial Homeostasismentioning
confidence: 99%
“…In contrast, the expression of genes related to hypoxia (such as Vegfa and Timp1 ) and chondrogenic markers ( Sox9 , Aggrecan , and Col2a1 ) was significantly upregulated (Figure 8c ). As shown in Figure 8c , genes (Actn2, Actn3, Slc25a4, Cav3) related to muscle contraction and ATP synthesis, [ 29 ] were significantly upregulated in the 3%‐Axitinib group. Considering muscle tissue is sensitive to the oxygen content in the microenvironment, [ 30 ] this increased transcriptional activity was likely an adaptive response of muscle tissue surrounding the engineered cartilage, to the hypoxia niche created by axitinib.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to P132L, a variety of other pathogenic mutations in caveolins have been identified in humans (12,44,45,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The most direct equivalent to P132L is a P105L mutation in CAV3 associated with muscular dystrophy (56,57).…”
Section: Discussionmentioning
confidence: 99%